2017
DOI: 10.18267/j.cebr.176
|View full text |Cite
|
Sign up to set email alerts
|

Does Unemployment and Precarious Employment Lead to Increasing Entrepreneurial Intentions among Young People? Results from a Survey-Based Study in Spain

Abstract: 1Vancea, M., Utzet, M.The article explores the relationship between unemployment and precarious employment, and young people's entrepreneurial intentions in Spain. We focus on the effects of employment conditions and experience on young people's intentions to start their own business or become selfemployed. The role of socio-demographic characteristics and behavioral factors such as perceived self-efficacy and desirability as well as risk taking were also analyzed. The analyses were based on a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In fact, several empirical studies confirmed that individuals with self-employed peers within their networks are more likely to become entrepreneurs (e.g. Vancea & Utzet, 2017). A person who managed to set up an own business acts as living evidence that entrepreneurial outcomes are achievable (DeClerq & Arenius, 2006), which in turn might act positively towards an individual's entrepreneurship inclination by reducing ambiguity regarding entrepreneurship (Minniti, 2005).…”
Section: What Drives Entrepreneurial Fear Of Failurementioning
confidence: 97%
“…In fact, several empirical studies confirmed that individuals with self-employed peers within their networks are more likely to become entrepreneurs (e.g. Vancea & Utzet, 2017). A person who managed to set up an own business acts as living evidence that entrepreneurial outcomes are achievable (DeClerq & Arenius, 2006), which in turn might act positively towards an individual's entrepreneurship inclination by reducing ambiguity regarding entrepreneurship (Minniti, 2005).…”
Section: What Drives Entrepreneurial Fear Of Failurementioning
confidence: 97%
“…In addition, although the importance of entrepreneurship has been acknowledged (Liñán et al, 2011), the role of contextual variations in discovering entrepreneurial intention and behaviour has been emphasised by many entrepreneurship scholars (Davidsson, 1995;Liñán & Chen, 2009;Mueller & Thomas, 2001;Hayton et al, 2002;Vancea & Utzet, 2017). Moreover, efforts to foster entrepreneurial activities, especially academic entrepreneurship, have been interested in both developed and developing countries, consisting of supported policy and programme by governments in many countries, some have had a positive effect, while others only have met with partial success (Baughn et al, 2006;Reynolds et al, 2001;Vodopivec, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, although EI is a fundamental element in entrepreneurship, it does not guarantee that one will venture into entrepreneurship, as it is highly dependent on various factors (e.g. cognitive, personality, environmental, social, educational, contextual, social, cultural and demographic factors) (Kruja-Demneri, 2020; Vancea and Utzet, 2017). Therefore, considering the above factors, considerable attention has been paid to determining the best-fit intent-based model for explaining EI and strengthening entrepreneurial participation (Maheshwari et al , 2022).…”
Section: Theory and Hypothesismentioning
confidence: 99%